LOKASI HALTE TRANS JOGJA DITINJAU DARI PERSPEKTIF AKSESIBILITAS PENGGUNA DALAM MENJANGKAUNYA - , HASRUL, Prof. Ir. bambang Hari Wibisono, MUP., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Yogyakarta is one of the big cities in Indonesia who attempting to overcomes its transportation problem by providing a mode of transportation called Trans Jogja. This new mode providers better services than others mode of transportation public. So far the existence of Trans Jogja has not be able to reduce transportation problem in this city. This condition is caused by the fact that the location of bus stops as a one of the most crucial component in operation of Trans Jogja is not appropriate. The location of bus stops are not in the centre of production and pull of passengers may be a reason why the society not using Trans Jogja optimally. This research aims to known the accessibility of Trans Jogja bus stops viewed by its passengers in this research, the passengers perspective are identified by three factors which include distance, travel time, and cost. This research used deductive approach, supported by both quantitative and qualitative techniques. The sample of this research consist of bus stop and users of Trans Jogja, with the number of sampel as many as 12, obtained by purposive method with catogorized them into four regions based on the types of surrounding activities include the education, trade, service and office area, hospital area, and tourism area. The sample number of Trans Jogja passengers were 120 people. The research shown that based on users perception of bus stop location accesibility, itâs known that in general the user states that the location of halt of Trans Jogja is currently better when viewed from distance, travel time and cost incurred within reach. In this case, distance factor become the most factor affected the accesibility of bus stop. People are not optimally used of Trans Jogja because the system did not provide maximum time realibility. A result people would prefer to use private transportation vehicles to support its activities, people tends to use Trans Jogja only when their trips are not timely constraints.